FIVE CORE VALUES REPRESENTED IN THE CHARACTERIZATION OF LITTLE BILLY IN DAHL’S BILLY AND THE MINPINS - Suwastini, Ni Komang Arie; Oktavirani, Ni Luh Gede Indah; Saputra, I Nyoman Pasek Hadi; Myartawan, I Putu Ngurah Wage; Jayantini, I Gusti Agung Sri Rwa (Universitas Negeri Makassar, 2025)
This study aimed to identify the values of character education in the main character in the novel for children entitled Billy and The Minpins. This study uses a qualitative interpretive method, in which close reading and note-taking are used to collect data from the plot structure in the story. The research procedure involves a repeated, simultaneous process of data collection, data condensation, data display, and conclusion drawing. The subject of this research is a novel, and the values of character education are the object of this research. The five core values of character education, as outlined by the Ministry of Education and Culture of Indonesia, were employed in this study. The findings of this study reveal that the characterization of Little Billy represents the five core values of character education: religious, nationalist, independence, cooperation, and integrity. These results suggest that children’s literature can offer examples of character education values for children, underscoring the potential of literary works as supplementary educational resources.